The Tradition of Rejectiveness: The Character of Responsibility in Islamic Education Values - Erik Fernando; Mohammad Baihaqi Bin Md Yusnan (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of the study: The aim of this research is to find out the values of Islamic education in the 1 Muharram Tradition which strengthen the character of community responsibility. Methodology: This research uses a qualitative approach with the people of kepahiang. The data collection techniques are observation, interview and documentation methods. The data analysis technique is triangulation, which involves comparing and cross-checking data from different sources and perspectives. Main Findings: The values of Islamic education in 1 Muharram can strengthen faith and piety and obedience to Allah SWT and always be grateful for the blessings that Allah has given. Local wisdom values can be found in various aspects of culture, such as language, art, literature, religion and customs . Local wisdom values can be used as values in Islamic education in any country, by integrating them with Islamic teachings and values, as long as they do not conflict with the Qur'an and Sunnah. In this way, Islamic education can benefit from the richness and diversity of local culture, and respect and preserve it. Islamic education can also increase the relevance and application of Islamic values in local contexts, as well as foster harmony and cooperation between Muslims and other communities and cultures. Local wisdom values can be used as values in Islamic education in any country, using various methods and strategies, such as curriculum development, teaching and learning activities, extracurricular programs, and community service. Novelty/Originality of this study: The novelty of this research lies in exploring and evaluating the potential benefits and dangers of a culture of rejection towards the development and enhancement of Islamic values and the character of responsibility in Islamic education, using a critical and comparative approach.